2011
DOI: 10.2320/matertrans.m2011048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ca on Tensile Properties and Stretch Formability at Room Temperature in Mg-Zn and Mg-Al Alloys

Abstract: The tensile tests and the Erichsen tests at room temperature have been performed on seven kinds of Mg alloys: Mg-1.5Zn, Mg-1.5Zn-0.1Ca, Mg-3Zn, Mg-3Zn-0.1Ca, Mg-3Al, Mg-3Al-0.1Ca and Mg-1Al-1Zn-0.1Ca-0.5Mn alloys. In the Mg-Zn alloys, the 0.2% proof stress at 90, which was the angle between the tensile direction and the RD, was decreased by addition of Ca, while the 0.2% proof stress at 0 was increased by addition of Ca. Also, an increase in elongation to failure by addition of Ca at 90 was larger than that at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
63
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 186 publications
(75 citation statements)
references
References 25 publications
(37 reference statements)
11
63
1
Order By: Relevance
“…The addition of Ca promoted grain refinement [32,33]. This may be because of the restriction of grain growth by the addition of Ca [17]. Precipitates were found in the Mg-Zn-X alloys from EPMA (results by EPMA are not shown in the present paper).…”
Section: Calculation Methodsmentioning
confidence: 68%
See 4 more Smart Citations
“…The addition of Ca promoted grain refinement [32,33]. This may be because of the restriction of grain growth by the addition of Ca [17]. Precipitates were found in the Mg-Zn-X alloys from EPMA (results by EPMA are not shown in the present paper).…”
Section: Calculation Methodsmentioning
confidence: 68%
“…Sandlö bes et al [38] investigated the dislocation motion in the Mg-3 mass% Y alloy deformed at room temperature and they found that the hc + ai slip is significantly enhanced by the Y addition. Our observation [17] revealed that prismatic hai and hci slips occur in the Mg-Zn-Ca alloy tensile-deformed to 1% [17]. Therefore, it is suggested that non-basal slips are enhanced by the addition of Ca, resulting in the tilting of basal texture in Mg-Zn-Ca alloys.…”
Section: Calculation Methodsmentioning
confidence: 72%
See 3 more Smart Citations